Peran Parenting Self-Efficacy dan Optimisme terhadap Psychological Well-Being Ibu yang Memiliki Anak Intellectual Disability - Nuri Ersy Pasyola; Asti Meiza Abdullah; Diah Puspasari (Psympathic : Jurnal Ilmiah Psikologi, 2021)
The presence of children will affect the lives of their parents. Parenting and educating Intellectual Disability (ID) children creates certain pressures, especially for mothers. Many mothers experienced stress and have feelings of uncertainty about their ability to care for which lead to pessimism. These stress and anxiety may have an impact on the psychological well-being of the mothers. The purpose of this study was to determine whether parenting self-efficacy and optimism affect the psychological well-being of mothers with ID children. This study used a quantitative approach with a causal correlational design. The research subjects were 43 mothers who had children with ID. The data was collected using a questionnaire consists of the Self-Efficacy for Parenting Index (SEPTI) adapted from Coleman and Karakker, optimism scale, and psychological well-being Scales (PWBS) adapted from Ryff. The results show that parenting self-efficacy and optimism had an effect on psychological well-being